Genome-Wide Analysis of Coding and Non-coding RNA Reveals a Conserved miR164–NAC–mRNA Regulatory Pathway for Disease Defense in Populus - Chen, Sisi; Wu, Jiadong; Zhang, Yanfeng; Zhao, Yiyang; Xu, Weijie; Li, Yue; Xie, Jianbo (Frontiers in Genetics, 2021)
MicroRNAs (miRNAs) contribute to plant defense responses by increasing the overall genetic diversity; however, their origins and functional importance in plant defense remain unclear. Here, we employed Illumina sequencing technology to assess how miRNA and mRNA populations vary in the Chinese white poplar (Populus tomentosa) during a leaf black spot fungus (Marssonina brunnea) infection. We sampled RNAs from infective leaves at conidia germinated stage [12 hpi], infective vesicles stage [24 hpi], and intercellular infective hyphae stage [48 hpi], three essential stages associated with plant colonization and biotrophic growth in M. brunnea fungi. In total, 8,938 conserved miRNA-target gene pairs and 3,901 Populus-specific miRNA-target gene pairs were detected. The result showed that Populus-specific miRNAs (66%) were more involved in the regulation of the disease resistance genes. By contrast, conserved miRNAs (> 80%) target more whole genome duplication (WGD)-derived transcription factors (TFs). Among the 1,023 WGD-derived TF pairs, 44.9% TF pairs had only one paralog been targeted by a miRNA that could be due to either gain or loss of a miRNA binding site after the WGD. A conserved hierarchical regulatory network that combining promoter analyses and hierarchical clustering approach uncovered a miR164-NAC-mRNA regulatory module that has potential in Marssonina defense responses. Furthermore, analyses of the locations of miRNA precursor sequences reveal that pseudogenes and transposon contributed a certain proportion (~30%) of the miRNA origin. Together, these observations provide evolutionary insights into the origin and potential roles of the miRNAs in plant defense and functional innovation.